Effects Of Anti-Stripping Additives On The Moisture Sensitivity Of Asphalt Mixtures Subjected To Several Conditioning Methods - Kam, Pui Kuan (Universiti Sains Malaysia, 2017)
Stripping is the most common cause of pavement distress in Malaysia. This could be attributed to the excessive infiltration of water into asphalt pavements which accelerate damage in both surface and subsurface layers. To minimize the problem, Tough Fix and ZycoTherm, which are currently used in Japan and India as anti-stripping agents and warm compaction additive respectively, were adopted. Each additive was incorporated in asphalt mixtures and then subjected to several moisture conditioning methods. To simulate the actual condition on site, moisture conditioning methods were carried out in a combination of aging and moisture intrusion. Different levels of moisture conditioning methods, ranging from unconditioned, moisture induced damage, modified Lottman, accelerated laboratory vacuum saturator and water immersion; were carried out to evaluate the engineering properties of asphalt mixtures in terms of indirect tensile strength and resilient modulus. From the mixture performance test results, mixtures prepared with ordinary portland cement (OPC), Tough Fix and ZycoTherm showed the potential to improve pavement resistance to pavement distresses such as moisture damage, permanent deformation and cracking. The effects of ZycoTherm on the ITSR, MR, fracture energy, workability, CEI and percentage of adhesive failure; were found to be significant. Analysis of fractured aggregate was one of the highlights of the study. Broken aggregates were extracted from the asphalt specimens to investigate the sources of failure. Apart from poor aggregate shapes such as flaky and elongated particles, aggregate orientation was one of the factors causing inconsistency of indirect tensile strength for certain specimens.